STUDI DESKRIPTIF MENGENAI PENGETAHUAN PERPAJAKAN DAN KEPATUHAN WAJIB PAJAK TERKAIT PAJAK PENGHASILAN PADA TIGA UMKM INDUSTRI MAKANAN DI KOTA BANDUNG - Soetanto, Natisha Nathaniaputeri; Muliawati, Muliawati (Universitas Katolik Parahyangan, 2024)
Tax is one of the main revenue source elements used for the benefit of a country. Most of the state revenue from taxes comes from income tax. One of the tax subjects that has the potential to make a significant contribution to tax revenue is the tax subject that runs Micro, Small and Medium Enterprises (MSMEs). In reality, this is not easy due to the possibility of various interpretations of taxation aspects among MSME actors, such as the low level of knowledge of tax obligations. There are many MSME actors who still pay little attention and are negligent towards tax obligations. The research method used in this research is descriptive qualitative. Primary data was collected using structured interview techniques. The object of this research is taxation knowledge and taxpayer compliance. The results of this study indicate that one MSME does not have comprehensive knowledge of the Income Tax obligations that must be fulfilled, while the two MSMEs show comprehensive knowledge of these obligations. The three MSMEs cannot be categorized as compliant taxpayers because they do not meet formal and material compliance.